Duality between coordinates and wave functions on noncommutative space - Vancea, Ion V (Physics letters. A, 2004)
The relation between coordinates and the solutions of the stationary Schrödinger equation in the noncommutative algebra of functions on R 2 N is discussed. We derive this relation for a certain class of wave functions for which the quantum prepotentials depend linearly on the coordinates similarly to the commutative case. Also, the differential equation satisfied by the prepotentials is given.